A critical review of structural supercapacitors and outlook on future research challenges - Greenhalgh,ES; Nguyen,S; Valkova,M; Shirshova,N; Shaffer,MSP; Kucernak,ARJ (Composites Science and Technology, 2023)
Structural composites and electrochemical energy storage underpin electrification of transportation, but advances in electric vehicles are shackled by parasitic battery mass. The emergence of structural power composites, multifunctional materials that simultaneously carry structural loads whilst storing electrical energy, promises dramatic improvements in effective performance Here, we assess the literature on structural supercapacitors, not only providing a comprehensive and critical review of the constituent (i.e., structural electrode, structural electrolyte and structural separator) developments, but also considering manufacture, characterisation, scale-up, modelling and design/demonstration. We provide a rigorous analysis of the multifunctional performance data reported in the literature, providing the reader with a detailed comparison between the different structural supercapacitor developments. We conclude with insights into the future research and adoption challenges for structural supercapacitors. There are several significant hurdles which must be addressed to mature this technology. These include development of a processable structural electrolyte; optimisation of current collection to facilitate device scale-up; identification of load-transmitting encapsulation solutions; standard protocols for characterisation and ranking of structural supercapacitors and; predictive multiphysics models for structural supercapacitors. Through addressing such issues, these emerging multifunctional materials will deliver a novel lightweighting strategy that can contribute to managing the ongoing climate crisis.